2018
DOI: 10.1016/j.eururo.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Low Free Testosterone and Prostate Cancer Risk: A Collaborative Analysis of 20 Prospective Studies

Abstract: BackgroundExperimental and clinical evidence implicates testosterone in the aetiology of prostate cancer. Variation across the normal range of circulating free testosterone concentrations may not lead to changes in prostate biology, unless circulating concentrations are low. This may also apply to prostate cancer risk, but this has not been investigated in an epidemiological setting.ObjectiveTo examine whether men with low concentrations of circulating free testosterone have a reduced risk of prostate cancer.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
95
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 41 publications
10
95
1
1
Order By: Relevance
“…9 Men with kidney disease are at higher risk of having a very low circulating testosterone concentration, 35 which in turn has been associated with a lower prostate cancer risk. 7 Findings from the present study showed that higher circulating urea and phosphate concentrations were associated with an increased prostate cancer risk, while cystatin-C and total protein circulating concentrations (both markers of kidney function) were associated with a lower risk. However, only the associations of cystatin-C and phosphate with risk were significant in the last four years of follow-up.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…9 Men with kidney disease are at higher risk of having a very low circulating testosterone concentration, 35 which in turn has been associated with a lower prostate cancer risk. 7 Findings from the present study showed that higher circulating urea and phosphate concentrations were associated with an increased prostate cancer risk, while cystatin-C and total protein circulating concentrations (both markers of kidney function) were associated with a lower risk. However, only the associations of cystatin-C and phosphate with risk were significant in the last four years of follow-up.…”
Section: Discussionmentioning
confidence: 43%
“…6 Moreover, men with low free testosterone concentrations may have a lower risk of overall prostate cancer. 7 However, the aetiology of prostate cancer is not well understood, and there is a need to identify novel risk factors for the disease.…”
Section: Introductionmentioning
confidence: 99%
“…KS, TH and hypopituitarism are conditions associated with clinically low testosterone concentrations . Low circulating testosterone concentrations may reduce prostatic androgen receptor signalling and may therefore reduce prostate cancer risk . In our analysis, there was no association with prostate cancer diagnosis in the combined hypogonadal cohort, although men diagnosed with KS had a 42% lower risk.…”
Section: Discussioncontrasting
confidence: 54%
“…Although there are large differences in global incidence rates, little is known regarding potentially modifiable risk factors. However, data from an international pooled individual‐level meta‐analysis of prospective studies have shown that high circulating insulin‐like growth factor‐I (IGF‐I) concentrations are associated with an increased risk of prostate cancer and that low free testosterone is associated with a reduced risk …”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have also reported an inverse association between prostate cancer risk and circulating SHBG 8 , although results from MR analyses are inconclusive 9 .…”
Section: Introductionmentioning
confidence: 99%